Variations of Colored Dissolved Organic Matter in the Mandovi Estuary, Goa, During Spring Inter-Monsoon: A Comparison With COVID-19 Outbreak Imposed Lockdown Period - Dias, Albertina; Kurian, Siby; Thayapurath, Suresh; Pratihary, Anil K. (Frontiers in Marine Science, 2021)
Colored dissolved organic matter (CDOM) is one of the important fractions of dissolved organic matter (DOM) that controls the availability of light in water and plays a crucial role in the cycling of carbon. High CDOM absorption in the Mandovi Estuary (Goa) during spring inter-monsoon (SIM) is largely driven by both in-situ production and anthropogenic activities. Here we presented the CDOM variation in the estuary during SIM of 2014 to 2018 and compared it with that of 2020 when the COVID-19 outbreak imposed lockdown was implemented. During 2020, low CDOM absorption was observed at the mid-stream of the estuary as compared to the previous years, which could be attributed to low autochthonous production and less input from anthropogenic activities. On the other hand, high CDOM observed at the mouth during 2020 is linked to the autochthonous production, as seen from the high concentrations of chlorophyll a. High CDOM in the upstream region could be due to both autochthonous production and terrestrially derived organic matter. Sentinel- 2 satellite data was also used to look at the variations of CDOM in the study region which is consistent with in-situ observations. Apart from this, the concentration of nutrients (NO3-, NH4+ and SiO44-) in 2020 was also low compared to the previous reports. Hence, our study clearly showed the impact of anthropogenic activities on CDOM build-up and nutrients, as the COVID-19 imposed lockdown drastically controlled such activities in the estuary.